If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6w + -12 = -9(w + 4) Reorder the terms: -12 + -6w = -9(w + 4) Reorder the terms: -12 + -6w = -9(4 + w) -12 + -6w = (4 * -9 + w * -9) -12 + -6w = (-36 + -9w) Solving -12 + -6w = -36 + -9w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '9w' to each side of the equation. -12 + -6w + 9w = -36 + -9w + 9w Combine like terms: -6w + 9w = 3w -12 + 3w = -36 + -9w + 9w Combine like terms: -9w + 9w = 0 -12 + 3w = -36 + 0 -12 + 3w = -36 Add '12' to each side of the equation. -12 + 12 + 3w = -36 + 12 Combine like terms: -12 + 12 = 0 0 + 3w = -36 + 12 3w = -36 + 12 Combine like terms: -36 + 12 = -24 3w = -24 Divide each side by '3'. w = -8 Simplifying w = -8
| 5c-8=3c | | 6/7g=42 | | 2s+15=4s-6 | | -5r-10=-9r+10 | | 5y+6+3y-12=180 | | -3(u+4)=6u+42 | | m/-104 | | 5x=-x+150 | | 10q+6=7q | | 8e^2x+2=5 | | -4(3)-3(-7)=9 | | 7v+21=2(v-2) | | m/-1009 | | -(1/3p)=1/4 | | (6/7)g=42 | | -3+2t=t | | 1.75m=15.75 | | 8(w-2)=-8w-16 | | -3x-14=-20 | | -g-10=10+4g | | -21=3/5x | | 3(4)x=42 | | 4x+8=3x-11 | | [5-4x]=-3 | | -36-12/5= | | 1/6x13 | | -8k+2k=6-5k | | -7w=-14/9 | | -119=7(2x-5) | | 4x^2+21x-16=19-2x | | 11/12-(10)-5/6 | | 14x-5=6x+2 |